Kajian Unsur Budaya Lampung dan Implikasinya Pada Pelaksanaan Konseling Lintas Budaya - Wibowo, Agus; Mudaim, Mudaim (STKIP Muhammadiyah Pringsewu, 2018)
The research aims to describe Lampung local wisdom and formulated of implication multicultural counseling for Lampung counselee. The research method used is qualitative. Informants are traditional Lampung figures. The research location on Lampung Tengah,Â Lampung Timur,Â and Bandar Lampung. Data collection using interviews and observation. The data were analyzed qualitatively by reducing the data, display data, and drawing conclusions. The result shows that the character of Lampung Society is based on the value of local wisdom is the Lampung society alway to be same or equal life from others, openness, good interaction to other, help each other, and respect people with other. Implications for cross-cultural counseling are: 1) in cross-cultural counseling, the courageous counselor should be open to using the